2020
DOI: 10.3390/foods9101500
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Intake of a Snack Containing Dietary Fiber on Postprandial Glucose Levels

Abstract: To examine the effects of the intake of a snack containing dietary fiber under free-living conditions on postprandial glucose levels in older adults, nine healthy older adults aged 76.9 ± 1.6 years (mean ± standard error) completed two crossover trials: 1) regular snack (BISCUIT) intake and 2) intake of snacks with a high dietary fiber content (DF-BISCUIT). In both trials, each participant consumed either BISCUIT or DF-BISCUIT between lunch and dinner time for 1 week. During the intervention, the blood glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
2
14
0
1
Order By: Relevance
“…Results suggest some reduction in postprandial glucose peaks at certain time points in the intervention group compared with placebo group. These results are in accord with recent studies that indicating significant lower blood glucose levels observed in test meals containing dietary fiber [ 31 33 ]. However, a higher blood glucose levels at 120 min in the intervention group could be attributed to the presence of slowly digestible starch in the formulated MMT peel powder belonging to the intervention group which digested between 20 min and 180 min [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…Results suggest some reduction in postprandial glucose peaks at certain time points in the intervention group compared with placebo group. These results are in accord with recent studies that indicating significant lower blood glucose levels observed in test meals containing dietary fiber [ 31 33 ]. However, a higher blood glucose levels at 120 min in the intervention group could be attributed to the presence of slowly digestible starch in the formulated MMT peel powder belonging to the intervention group which digested between 20 min and 180 min [ 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the next experiment, we examined the characteristics of the two shorter and longer groups. The shorter starvation group showed higher physical activity [21], higher dietary ber intake [19,20], and a tendency towards morningness in the MEQ score [21]. These tendencies are related to a reduction in blood glucose levels.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, it was shown that the consumption of dietary fiber causes fermentation via colonic microbiota, which produce short-chain fatty acids. This was shown to increase the viscosity of stomach contents, slow down the rate of gastric emptying, and prolong glucose absorption, which could slow the rate of the absorption of glucose molecules into the intestine, improve insulin function, and lower glycemic loads [38,39]. Therefore, the intake of more dietary fiber at dinner agrees with biological rhythms.…”
Section: Discussionmentioning
confidence: 97%